2010
DOI: 10.4088/jcp.08m04942gre
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled Study of Quetiapine and Paroxetine as Monotherapy in Adults With Bipolar Depression (EMBOLDEN II)

Abstract: clinicaltrials.gov Identifier: NCT00119652.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
246
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(264 citation statements)
references
References 47 publications
12
246
0
5
Order By: Relevance
“…Pooled analyses of five identically designed trials demonstrated that quetiapine was superior to placebo, and moreover was equally effective for acute depression in BDI and BDII 243, 437. The latter finding must be reconciled with the fact that quetiapine beat placebo in only three of the five individual trials in patients with BDII, compared to all five in patients with BDI 253, 290, 438, 439, 440. This is probably because the smaller sample of BDII patients—only about half as many patients with BDII as BDI were enrolled in each of the trials—provided less statistical power for BDII.…”
Section: Bipolar II Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Pooled analyses of five identically designed trials demonstrated that quetiapine was superior to placebo, and moreover was equally effective for acute depression in BDI and BDII 243, 437. The latter finding must be reconciled with the fact that quetiapine beat placebo in only three of the five individual trials in patients with BDII, compared to all five in patients with BDI 253, 290, 438, 439, 440. This is probably because the smaller sample of BDII patients—only about half as many patients with BDII as BDI were enrolled in each of the trials—provided less statistical power for BDII.…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…Antidepressants should not be used as monotherapy in patients with BDI depression, as available trials do not support their efficacy and there are concerns about their safety in terms of mood switching (level 2 negative) 260, 289, 290, 291…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NICE [16] and CANMAT [11] guidelines now recommend QTP as the first-line drug, especially for the more severe pathophysiology of acute mania, due to its rapid and potent antimanic effects. Meanwhile, the efficacy of QTP monotherapy in acute bipolar depression has been consistently confirmed by such double-blind, placebo-controlled studies as BOLDER (BipOLar DEpRession) I/II [8,20] and EMBOLDEN (Efficacy of Monotherapy SEROQUEL in BipOLar DEpressioN) I/II [17,21]. The latter EMBOLDEN studies also examined the efficacy of QTP monotherapy in relapse prevention for bipolar disorders, and the results suggested that the preventive effect of QTP monotherapy is superior to that of placebo for both manic and depressive recurrence, and is superior to that of Li for depressive recurrence [11], and that the efficacy of Li or VPA for relapse prevention of any mood episode is clearly augmented by QTP coadministration [10,22].…”
Section: Qtpmentioning
confidence: 84%
“…32 In 2007, a large trial found no benefit associated with the addition of paroxetine or bupropion to a mood stabiliser; 33 another reported that paroxetine was no better at achieving a durable recovery than placebo. 34 A recent updated meta-analysis of antidepressants in bipolar depression reported a pooled effect no different from placebo (relative risk [RR] of response 1·17, 95% CI 0·82-1·57) with statistically significant heterogeneity. 35 Meta-analyses in patients with bipolar disorder have grouped antidepressant drugs together as one class, despite the observed statistically significant heterogeneity and the evidence in patients with unipolar disorder that antidepressant agents vary to a clinically significant degree in both efficacy and tolerability.…”
Section: Treatment Of Bipolar Depressionmentioning
confidence: 99%